Implementing Indigenous rights through climate–health governance: advancing the Indigenous Determinants of Health framework within the UNFCCC - Roth, Geoffrey Scott; Bermudez Del Villar, Alejandro; Amharech, Amina; Forrest, Lala; Carvalho, Matthew (Frontiers in Climate, 2025)
As the UNFCCC evolves, the urgency to advance Indigenous Peoples’ Rights within global climate governance has never been greater. COP 30 offers a powerful starting point to embed reforms that center Indigenous leadership, rights and knowledge systems. This article proposes integrating the Indigenous Determinants of Health (IDH) Framework into UNFCCC processes to realize Indigenous Rights as affirmed by UNDRIP and the Paris Agreement. Drawing on CBD Decision 16/19, we highlight entry points in the Global Stocktake, the Gender Action Plan and the national adaptation planning, alongside five additional mechanisms on adaptation, finance, and loss and damage. We argue the IDH provides a rights-based structure for implementing Article 7.5 of the Paris Agreement and ensuring alignment with UNDRIP, FPIC and cultural safety.